AQP4-AS1 Can Regulate the Expression of Ferroptosis-Related Regulator ALOX15 through Competitive Binding with miR-4476 in Lung Adenocarcinoma - Du, Lin; Xu, Geng; Zhang, Xiuqiang; Zhang, Zhiwei; Yang, Yang; Teng, Hongsheng; Yang, Tao (Global Medical Genetics, 2024)
Background The AQP4-AS1/miR-4476-ALOX15 regulatory axis was discovered in previous studies. We aimed to investigate the regulatory mechanism of the ferroptosis-related regulator ALOX15 by AQP4-AS1 and miR-4476 in lung adenocarcinoma (LUAD) and find new targets for clinical treatment.Methods After bioinformatics analysis, we contained one ferroptosis-related gene (FRG), namely ALOX15. MicroRNAs (miRNAs) and long noncoding RNAs were predicted by miRWalk. Furthermore, we constructed overexpressed LUAD cell lines. Real-time quantitative polymerase chain reaction and western blot were used to determine the expression of mRNA and protein, respectively. Cell Counting Kit-8 (CCK-8) and EdU assay were used to detect the cell proliferation. Double luciferase assay was used to detect the binding relationship between AQP4-AS1 and miR-4464.Results ALOX15 was the most significantly downregulated FRG compared with normal tissues. Furthermore, protein-protein interaction network analysis indicated that the AQP4-AS1-miR-4476-ALOX15 regulatory axis might be involved in the occurrence and development of LUAD and there might be direct interaction between AQP4-AS1 and miR-4476, and miR-4476 and ALOX15. Furthermore, AQP4-AS1 and ALOX15 were significantly downregulated in the LUAD tissue and cell lines, whereas miR-4476 showed the opposite results (p < 0.001). AQP4-AS1 overexpression improved the ALOX15 expression in LUAD cell lines. CCK-8 and EdU assay revealed that overexpression of AQP4-AS1 and ALOX15 inhibited the LUAD cell proliferation. Double luciferase assay results indicated that there was a combination between AQP4-AS1 and miRNA-4476. In addition, we found that overexpressed AQP4-AS1 activates the ferroptosis in LUAD cell lines.Conclusions AQP4-AS1 can regulate the expression of ALOX15 through competitive binding with miR-4476, further activate ferroptosis and inhibit the proliferation of LUAD cells.
Keywords: lung adenocarcinoma; ALOX15; ferroptosis; AQP4-AS1; miRNA-4476